How do you solve \[7(2x + 5) = 4x - 9 - x\;?\]
Answer
Verified
442.8k+ views
Hint: We will multiply and subtract all the variables and constant terms separately and then we will calculate the value of \[x\]. On doing some calculation we get the required answer.
Formula used: If an equation contains a single variable in the following format, we can calculate the value of the variable in the following way.
Let's say, \[A(mx + n) = c\] is the given equation and we have to calculate the value of \[x\].
So, we can interpret the equation in following way:
\[ \Rightarrow Amx + An = c\].
Now, we can take the constant terms in R.H.S:
\[ \Rightarrow Amx = c - An\].
So, we can get the value of \[x\] by dividing the constant term by the coefficient of \[x\].
\[ \Rightarrow x = \dfrac{{c - An}}{{Am}}\].
Complete Step by Step Solution:
The given equation is \[7(2x + 5) = 4x - 9 - x\;.\]
Now, by subtracting the variables on the R.H.S, we get:
\[ \Rightarrow 7(2x + 5) = 3x - 9\].
Now, by doing the multiplication on L.H.S, we get:
\[ \Rightarrow 14x + 35 = 3x - 9.\]
Now, take the constant term on R.H.S and the variable term on L.H.S, we get:
\[ \Rightarrow 14x - 3x = - 35 - 9.\]
Now, perform the required operations on R.H.S and L.H.S, we get the following equation:
\[ \Rightarrow 11x = - 44.\]
Now, divide the constant term on L.H.S by the coefficient of\[x\] on R.H.S, we get:
\[ \Rightarrow x = \dfrac{{ - 44}}{{\;\;11}}.\]
Now, perform the division on R.H.S, we get:
\[ \Rightarrow x = - 4.\]
Therefore, the value of \[x\] or the solution of the equation is \[ - 4\].
Note: Alternate way to solution:
The given equation is\[7(2x + 5) = 4x - 9 - x\;.\]
We can divide both the sides of the equation by \[7\].
SO, by performing it, we get:
\[ \Rightarrow 2x + 5 = \dfrac{{4x - 9 - x}}{7}\].
Now, by solving on the R.H.S, we get:
\[ \Rightarrow 2x + 5 = \dfrac{{3x - 9}}{7}\].
Now, further splitting up the terms in R.H.S, we get:
\[ \Rightarrow 2x + 5 = \dfrac{{3x}}{7} - \dfrac{9}{7}\].
Now, taking the variable terms on L.H.S and constant terms on R.H.S, we get:
\[ \Rightarrow 2x - \dfrac{{3x}}{7} = - 5 - \dfrac{9}{7}\].
Now, by doing the subtractions on both the sides, we get:
\[ \Rightarrow \dfrac{{14x - 3x}}{7} = \dfrac{{ - 35 - 9}}{7}\].
Now, simplify it further:
\[ \Rightarrow \dfrac{{11x}}{7} = \dfrac{{ - 44}}{7}\].
Now, cancel out the same terms on the denominators, we get:
\[ \Rightarrow 11x = - 44.\]
By doing the division, we get:
\[ \Rightarrow x = \dfrac{{ - 44}}{{\;\;11}}\]
\[ \Rightarrow x = - 4.\]
\[\therefore \]The solution of the equation is \[x = - 4.\]
Formula used: If an equation contains a single variable in the following format, we can calculate the value of the variable in the following way.
Let's say, \[A(mx + n) = c\] is the given equation and we have to calculate the value of \[x\].
So, we can interpret the equation in following way:
\[ \Rightarrow Amx + An = c\].
Now, we can take the constant terms in R.H.S:
\[ \Rightarrow Amx = c - An\].
So, we can get the value of \[x\] by dividing the constant term by the coefficient of \[x\].
\[ \Rightarrow x = \dfrac{{c - An}}{{Am}}\].
Complete Step by Step Solution:
The given equation is \[7(2x + 5) = 4x - 9 - x\;.\]
Now, by subtracting the variables on the R.H.S, we get:
\[ \Rightarrow 7(2x + 5) = 3x - 9\].
Now, by doing the multiplication on L.H.S, we get:
\[ \Rightarrow 14x + 35 = 3x - 9.\]
Now, take the constant term on R.H.S and the variable term on L.H.S, we get:
\[ \Rightarrow 14x - 3x = - 35 - 9.\]
Now, perform the required operations on R.H.S and L.H.S, we get the following equation:
\[ \Rightarrow 11x = - 44.\]
Now, divide the constant term on L.H.S by the coefficient of\[x\] on R.H.S, we get:
\[ \Rightarrow x = \dfrac{{ - 44}}{{\;\;11}}.\]
Now, perform the division on R.H.S, we get:
\[ \Rightarrow x = - 4.\]
Therefore, the value of \[x\] or the solution of the equation is \[ - 4\].
Note: Alternate way to solution:
The given equation is\[7(2x + 5) = 4x - 9 - x\;.\]
We can divide both the sides of the equation by \[7\].
SO, by performing it, we get:
\[ \Rightarrow 2x + 5 = \dfrac{{4x - 9 - x}}{7}\].
Now, by solving on the R.H.S, we get:
\[ \Rightarrow 2x + 5 = \dfrac{{3x - 9}}{7}\].
Now, further splitting up the terms in R.H.S, we get:
\[ \Rightarrow 2x + 5 = \dfrac{{3x}}{7} - \dfrac{9}{7}\].
Now, taking the variable terms on L.H.S and constant terms on R.H.S, we get:
\[ \Rightarrow 2x - \dfrac{{3x}}{7} = - 5 - \dfrac{9}{7}\].
Now, by doing the subtractions on both the sides, we get:
\[ \Rightarrow \dfrac{{14x - 3x}}{7} = \dfrac{{ - 35 - 9}}{7}\].
Now, simplify it further:
\[ \Rightarrow \dfrac{{11x}}{7} = \dfrac{{ - 44}}{7}\].
Now, cancel out the same terms on the denominators, we get:
\[ \Rightarrow 11x = - 44.\]
By doing the division, we get:
\[ \Rightarrow x = \dfrac{{ - 44}}{{\;\;11}}\]
\[ \Rightarrow x = - 4.\]
\[\therefore \]The solution of the equation is \[x = - 4.\]
Recently Updated Pages
Glucose when reduced with HI and red Phosphorus gives class 11 chemistry CBSE
The highest possible oxidation states of Uranium and class 11 chemistry CBSE
Find the value of x if the mode of the following data class 11 maths CBSE
Which of the following can be used in the Friedel Crafts class 11 chemistry CBSE
A sphere of mass 40 kg is attracted by a second sphere class 11 physics CBSE
Statement I Reactivity of aluminium decreases when class 11 chemistry CBSE
Trending doubts
When people say No pun intended what does that mea class 8 english CBSE
In Indian rupees 1 trillion is equal to how many c class 8 maths CBSE
How many ounces are in 500 mL class 8 maths CBSE
Which king started the organization of the Kumbh fair class 8 social science CBSE
What is BLO What is the full form of BLO class 8 social science CBSE
Advantages and disadvantages of science